Assessing The Readiness of Local Governments for Sustainability Reporting in Indonesia: A Policy and Institutional Analysis - Amrie Firmansyah; Zubir Azhar (IPSAR (International Public Sector Accounting Review), 2025)
This study assesses the readiness of local governments in Indonesia to implement sustainability reporting within the framework of public accountability and institutional change. Using a scoping review approach, the analysis covers fifteen national and international documents, including key regulatory frameworks and reporting standards. The dataset consists of Indonesia's core policy instruments—such as Law No. 23/2014, Law No. 1/2022, Law No. 59/2024 on the National Long-Term Development Plan (RPJPN) 2025–2045, Presidential Regulation No. 12/2025 on the National Medium-Term Development Plan (RPJMN) 2025–2029, and the Environmental Strategic Assessment (KLHS RPJPN 2023)—as well as global references from the International Public Sector Accounting Standards Board (IPSASB), the International Federation of Accountants (IFAC), and the Organisation for Economic Co-operation and Development (OECD). The findings indicate that Indonesia has developed a strong national policy foundation supporting sustainable governance; however, at the subnational level, sustainability reporting remains conceptual and fragmented. Institutional barriers, including weak inter-agency coordination, disconnected data systems, and limited human resource capacity, hinder implementation. Existing accountability mechanisms, such as LPPD and LAKIP, continue to prioritize administrative compliance over environmental, social, and governance (ESG) impacts. Additionally, the study concludes that Indonesia's public sector exhibits normative alignment with global frameworks (IFRS S1–S2, IPSASB, and IFAC), but lacks operational institutionalization at the local level. Sustainability reporting has not yet transitioned from a compliance-oriented tool into an integrated accountability mechanism. Advancing sustainability accountability in local governance requires stronger institutional coordination, professional capacity building, and data system integration consistent with public sector reporting reforms led by the Government Accounting Standards Committee (Komite Standar Akuntansi Pemerintahan, KSAP).